Reporting of Adverse Drug Reactions: A Study Among Cinicians - Lisha Jenny John, Mohamed Arifulla, Jenny Cheriathu, Jayadevan Sreedharan (Journal of Applied Pharmaceutical Science)
Spontaneous reporting of ADRs enhances detection of serious, unexpected and unusual ADRs. Healthcare professionals play an integral role in the success of safety surveillance of drugs. This study aimed to investigate knowledge, practice and factors affecting ADR reporting among clinicians. Cross sectional study was carried out among clinicians of a tertiary care centre irrespective of their gender, specialization and experience. A validated self administered questionnaire was distributed among clinicians to assess the knowledge, practice and factors influencing ADR reporting. The 42 clinicians participated in the study comprised more than 50% males, had a mean age 36+8 years and represented a multi-ethnic population of varying clinical experience. With regard to ADR reporting, majority of the clinicians correctly identified which of the ADRs had to be reported and the individuals who can report ADRs. Very few clinicians had reported ADRs to the Pharmacovigilance Centre. The common factor discouraging reporting of ADR was not knowing how to report ADRs (71%). A majority of the clinicians were willing to undergo training on this aspect. The study revealed under-reporting of ADRs, and the willingness of clinicians to be trained in ADR reporting thus contributing to Pharmacovigilance program.
Keywords: adverse drug reactions,clinicians,UAE.